Integration methodology for feature-based modeling and recognition - Ko, H.; Park, M.-W.; Kang, H.; Sohn, Y.; Kim, H.S. (ASME 1993 International Computers in Engineering Conference and Exposition, CIE 1993, 1993)
This paper presents an integration method that constructs a feature model either by inserting new features or by recognizing features from existing geometric model. The integration is made possible by keeping the feature model data structure that is identical whether constructed by the feature insertion or the recognition. This overcomes the representational mismatch between the procedural feature-based modeling framework and the feature recognition framework. The integrated framewoik has been implemented as a CADCAM system for mould die manufacturing, which can interactively modify the geometric model by deleting recognized features. ？ 1993 ASME 1993 International Computers in Engineering Conference and Exposition, CIE 1993. All rights reserved.